An evaluation of the industry-academe-government collaboration for the Philippine Coffee Industry - Lorenzana, Edelle A. (University of the Philippines Diliman, 2006)
The Philippines was once renowned globally as a powerhouse producer of premium coffee beans, becoming the fourth largest coffee exporter in the world by the close of the 1900s. Despite a coffee rust infestation that adversely affected crop production in the mid-1900s, the Philippine Coffee Industry bounced back and reached a newer peak in 1986 with earnings level of USD150 million, a huge USD132 million of which was brought in from export revenues alone. Regrettably, the succeeding years saw a steady decline in the industry's performance, and in 2001, the country's coffee export value was pegged at a paltry USD500,000. Arable coffee farms, in turn, decreased 50 percent from a 1986 peak of 160,000 hectares. The Philippines is now merely an industry player by recall rather than by active participation in the world coffee market. Despite possession of a key source of competitive advantage, the "Kapeng Barako," a specialty bean variety that grows in only three countries, the local coffee industry continues to experience and shows little sign of resistance to a potential significant fall in production, what with the shifting of coffee farmers to other crops, and the possible extinction of the Barako variety. The sector has been largely neglected for years now, as the industry suffers from antiquated farming skills and lack of credit support. Add to this the decrease in world prices for coffee beans, and it seems that to describe growing coffee in the Philippines as an unprofitable enterprise is an understatement. Despite this and the fact that most growers have diversified to high-value crops or have converted their lands to commercial or industrial use, there exist a handful of idealists. A group of coffee growers, coffee retailers, and a newly-formed government institution, have started and are actively pursuing the fulfillment of a national mission-to revitalize the Philippine Coffee Industry and bring it back to its previously world-renowned status as a source of premium coffee. The battlecry for industry revival became imperative insofar as multi-sectoral benefits are projected to be achieved, such as savings from decreased import volume, generation of export earnings that would contribute to national economic growth, global prominence in marketing the specialty Philippine Coffee, and the optimization of farmlands and agricultural assets. Leading the way is a group of trailblazing entities : the town government of Amadeo, Cavite, where the Kapeng Barako is most prolifically grown; Figaro Coffee Company, the private sector lead in this collaboration and one of the country's leading coffee retailers; the National Coffee Development Board, the private-sector led but government-created task force mandated by the President to revitalize the industry; and the Cavite State University, where research and cultivation on the Liberica bean serve as primary raw material. The collaborative initiatives from the industry, academe and government stakeholders are numerous and quite notable in its multi-faceted approach to resurrecting this ailing industry. From the Marketing standpoint, the Industry-Government partnership came into prominence as it launched promotional campaigns to bring Philippine Coffee back into the public's attention. Figaro Coffee Company launched the Save the Barako awareness campaign and farm tours. The National Coffee Development Board, in turn, led the creation of a national seal of excellence, the "Kape Isla" brand whereby all 100 percent Philippine produced coffee will be marked. The town government of Amadeo Cavite instituted the annual Pahimis Festival to promote their local coffee industry and attract investors. The Industry-Academe relationship also contributed to the marketing effort by putting up pilot organic coffee farms, to cater to the niche market for naturally-grown produce. On the Academe-Government front, plans to establish a local specialty retail coffee shop, parallel to the likes of Starbucks, was commissioned by the Cavite governor and studied by the local university. On the Financing front, Industry-Government ingenuity took the lead with the Adopt-A-Farm project, a farming-investment arrangement between private individual investors and coffee farm owners. The national government, through a special decree by the President of the Philippines, offered loan availments to coffee growers, while Nestle, the multinational private stakeholder, infused foreign capital for the cultivation of coffee agribusiness in the country. To boost the industry's Operations, the Industry-Academe alliance made available low-cost, high-yield seedlings to farmers. More importantly, agronomy seminars and trainings have also been continually offered, with funding coming from the industry partners and expertise coming from the academe stakeholders. This setup also provided for the creation of pilot research farms, for both Barako and Organic Arabica coffee, and tree-planting activities to increase the number of productive farmlands. The Industry-Government efforts included the promotion of quality coffee production through the "Kape Isla" seal, and active participation in both international and local trade fairs which constantly exposed the Philippine Coffee Industry to innovative and efficient methods of production. From the Regulatory standpoint, collaborative initiatives were limited to Industry-Government efforts in the form of municipality-led ordinances in the town of Amadeo, Cavite, as well as the provision of credit by the national Department of Agriculture. The challenge facing the industry is humongous and progress may not be as rapid as would be desired. Some of success may be measured, however, in how the Industry-Academe-Government collaboration has alleviated the plight of the Philippine Coffee Industry. On land utilization, the tree-planting activities and government-mandated farm rejuvenation programs have increased the number of fruit-bearing trees in the coffee-growing regions. On infrastructure improvements, the infusion of capital from both private and public sectors has allowed for more efficient and sustainable farming methods and machineries. On the stability of production, coffee export earnings have increased steadily since 2003, when the collaboration effort started, from USD500,000 in 2000 to USD5.3 million in 2005. On people development, both coffee grower and coffee consumer have benefited from seminars, trainings and technology transfer activities that were jointly sponsored by the stakeholders. On market recognition, Philippine Coffee is slowly regaining distinction in the world coffee map, through the relentless promotion of both Kapeng Barako and Organic Mountain Arabica. Lastly, on government support, strategic development plans have been initiated in key coffee-growing regions. The key success factors of the collaboration come not from the tangible effects of the alliance itself, but rather from the characteristics and approaches taken by the collaborating entities. The Industry players contributed their marketing, promotional and distribution expertise that enhanced both marketability and delivery of the product; the Academe provided grassroots and technical knowledge that will ensure continuous product and process improvement in coffee production; while the Government bestowed the minimum level of support towards the collaboration endeavor. Though the Philippine Coffee Industry is making headway towards growth, its full rehabilitation is still, by and large, a thing of the future. There is still much work to be done by the stakeholders to ensure peak industry performance and reap maximum benefits for all collaborating participants. As a recommendation, further activities on branding and market niches should be pursued, such as capitalizing on the nation's indigenous specialty coffee varieties, rebranding of the quality seal, increasing attendance in world trade fairs, professionalizing the business of coffee brewing, and promoting the product's health benefits. In marketing Philippine Coffee, Industry chiefly participates through the effective promotion of brands, specialty coffee products and other awareness campaigns, while the Government offers support through the institution of quality standards, credit funding structures and tax incentives. In a secondary but no less important role, the Academe should also be consulted to determine new product and process trends that might affect the branding campaign. To boost financing and the infusion of capital, collaboration endeavors should focus on a more aggressive agro-tourism program that will sustain the industry's growth and attract investors, a better-structured credit funding facility from the national government, and the increase of millers and farming cooperatives that could distribute loan grants. In this financial aspect, it is the Government who will play a key role in the generation and accessibility of capital, the decentralization of state support through local government units, and the provision of incentives and tax breaks. The Academe and Industry will assist through information gathering and dissemination. Initiatives to improve operations and technology should establish national connoisseurship standards to ensure quality production, the use of e-commerce to facilitate information exchange and trading, and the institutionalization of certification programs for coffee growers. In enhancing the operational aspect, the Academe spearheads the activities through proactive research and development that will pinpoint the best implementation strategy for product and process improvements. The Industry and Government will then work together to apply the innovations across the coffee supply chain. Regulations and government support should be severely enhanced to include more responsive state-led policies and incentives, as well as the sponsorship of national surveys